Synaptic activity and strength are reflected by changes in the post-synaptic secretory pathway - Clara-Marie Gürth (Nature Portfolio, 2020)
Abstract Neurons are highly asymmetric cells that span long distances and need to react promptly to local demands. Consequently, neuronal secretory pathway elements are distributed throughout neurites, specifically in post-synaptic compartments, to enable local protein synthesis and delivery. Whether and how changes in local synaptic activity correlate to post-synaptic secretory elements is still unclear. To assess this, we used STED nanoscopy and automated quantitative image analysis of post-synaptic markers of the endoplasmic reticulum, ER-Golgi intermediate compartment, trans-Golgi network, and spine apparatus. We found that the distribution of these proteins was dependent on pre-synaptic activity, measured as the amount of recycling vesicles. Moreover, their abundance correlated to both pre- and post-synaptic markers of synaptic strength. Overall, the results suggest that in small, low-activity synapses the secretory pathway components are tightly clustered in the synaptic area, presumably to enable rapid local responses, while bigger synapses utilise secretory machinery components from larger, more diffuse areas.